Utility of electrocardiogram to predict the occurrence of the no-reflow phenomenon in patients undergoing primary percutaneous coronary intervention (PPCI): a systematic review and meta-analysis - Jafari Afshar, Elmira; Gholami, Niloofar; Samimisedeh, Parham; MozafaryBazargany, MohammadHossein; Tayebi, Amirhossein; Memari, Amirhossein; Yazdani, Shahrooz; Rastad, Hadith (Frontiers in Cardiovascular Medicine, 2024)
Background The no-reflow phenomenon affects about one out of five patients undergoing Primary Percutaneous Coronary Intervention (PPCI). As the prolonged no-reflow phenomenon is linked with unfavorable outcomes, making early recognition is crucial for effective management and improved clinical outcomes in these patients. Our review study aimed to determine whether electrocardiogram (ECG) findings before PCI could serve as predictors for the occurrence of the no-reflow phenomenon. Methods and materials We systematically searched MEDLINE, Scopus, and Embase to identify relevant studies. The random-effect model using inverse variance and Mantel-Haenszel methods were used to pool the standardized mean differences (SMD) and odds ratios (OR), respectively. Result Sixteen eligible articles (1,473 cases and 4,264 controls) were included in this study. Based on our meta-analysis of baseline ECG findings, the no-reflow group compared to the control group significantly had a higher frequency of fragmented QRS complexes (fQRS) (OR (95% CI): 1.35 (0.32–2.38), P-value = 0.01), and Q-waves (OR (95% CI): 1.97 (1.01–2.94), P-value <0.001). Also, a longer QRS duration (QRSD) (SMD (95% CI): 0.72 (0.21, 1.23), p-value <0.001) and R wave peak time (RWPT) (SMD (95% CI): 1.36 (0.8, 1.93), P < 0.001) were seen in the no-reflow group. The two groups had no significant difference regarding P wave peak time (PWPT), and P wave maximum duration (Pmax) on baseline ECG. Conclusion Our findings suggest that prolonged QRSD, delayed RWPT, higher fQRS prevalence, and the presence of a Q wave on baseline ECG may predict the occurrence of the no-reflow phenomenon in patients undergoing PPCI.